KDRT DALAM FILM LINGKARAN KEKERASAN - Hidayat, Nur (Seni Media Rekam ISI Surakarta, 2016)
Film Cycle ofViolence tells us a tale of a wife named Jelita Nawangsari who experiencedmarital violence by her own husband.Like its namesake title,the pattern of violence itself doesnot necessarily happen all the time but recourses alongside moments of peace,even pleasantful.In this film, languages no longer merely exist as a tool to portray a reality, but also to defineimages of a media reality within the minds of common folk.Through film languages ( symbols ),verbals not only took form of written and spoken words,but also of pictures,photos,graphics,movements and etc. to allow the media ( film ) to become reality – constructing apparel, asperceived by the artist.Keywords: Film,pattern,the cycle of violence,film languages,and reality